On English proverb variation from the perspective of linguistic creativity - Wu, Jianhao; Zhou, Wanting; Shao, Bin (Frontiers in Psychology, 2023)
Proverbs are usually regarded as structurally fixed expressions. However, in the daily communication, language users often change them to suit their communicative purposes in many ways, resulting in proverb variations. Using the data from COCA corpus, this paper attempts to present varieties of the English proverb “There are two sides to every coin” and explain the variations from the perspective of linguistic creativity. This paper also explores the variations of this proverb in EFL learners’ use via the data from Chinese EFL learners’ corpus TECCL. The study shows that, firstly proverb use can roughly be divided into two types: canonical and non-canonical use, each having three ways of alteration, i.e., addition of modifiers, substitution of content words, and reduction. Secondly, Chinese EFL learners tend to use the proverb in a mechanical way with little variation, which shows their inflexible use of proverbs. Finally, by nature proverb variation is the creative manipulation of use to fit the context, which is a form of linguistic creativity that reflects the cognitive creativity of human beings.